N(…)C and S(…)S Interactions in Complexes, Molecules, and Transition Structures HN(CH)SX:SCO, for X = F, Cl, NC, CCH, H, and CN - Del Bene, Janet E. (Molecules, 2019)
Ab initio Møller–Plesset perturbation theory (MP2)/aug’-cc-pVTZ calculations have been carried out in search of complexes, molecules, and transition structures on HN(CH)SX:SCO potential energy surfaces for X = F, Cl, NC, CCH, H, and CN. Equilibrium complexes on these surfaces have C(1) symmetry, but these have binding energies that are no more than 0.5 kJ·mol(–1) greater than the corresponding C(s) complexes which are vibrationally averaged equilibrium complexes. The binding energies of these span a narrow range and are independent of the N–C distance across the tetrel bond, but they exhibit a second-order dependence on the S–S distance across the chalcogen bond. Charge-transfer interactions stabilize all of these complexes. Only the potential energy surfaces HN(CH)SF:SCO and HN(CH)SCl:SCO have bound molecules that have short covalent N–C bonds and significantly shorter S(…)S chalcogen bonds compared to the complexes. Equation-of-motion coupled cluster singles and doubles (EOM-CCSD) spin-spin coupling constants (1t)J(N–C) for the HN(CH)SX:SCO complexes are small and exhibit no dependence on the N–C distance, while (1c)J(S–S) exhibit a second-order dependence on the S–S distance, increasing as the S–S distance decreases. Coupling constants (1t)J(N–C) and (1c)J(S–S) as a function of the N–C and S–S distances, respectively, in HN(CH)SF:SCO and HN(CH)SCl:SCO increase in the transition structures and then decrease in the molecules. These changes reflect the changing nature of the N(…)C and S(…)S bonds in these two systems.